2021
DOI: 10.3389/fncel.2021.569424
|View full text |Cite
|
Sign up to set email alerts
|

TMAO Aggregates Neurological Damage Following Ischemic Stroke by Promoting Reactive Astrocytosis and Glial Scar Formation via the Smurf2/ALK5 Axis

Abstract: Ischemic stroke has been reported to cause significant changes to memory, thinking, and behavior. Intriguingly, recently reported studies have indicated the association of Trimethylamine N-oxide (TMAO) with the acute phase of ischemic stroke. However, the comprehensive underlying mechanism remained unknown. The objective of the present study was to investigate the association between TMAO and recovery of neurological function after ischemic stroke. For this purpose, a middle cerebral artery occlusion/reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…The primary focus of this work was on the effects of TMAO upon the BBB, but this is not necessarily the only CNS target for the methylamine. Our data add to the evidence suggesting that astrocytes [ 66 , 67 ] and microglia [ 68 , 69 ] may respond to TMAO treatment, although it is notable that previous studies have shown pro-activating effects of TMAO at supra-physiological concentrations (> 50 μM). An intriguing finding of the current study is the brain region selectivity in the effects of long-term LPS and/or TMAO treatment upon parenchymal glia, with astrocytes and microglia of the entorhinal cortex showing clear LPS-induced, TMAO-sensitive activation, whereas the same cell types in the neighbouring hippocampus appeared resistant to either stimulus.…”
Section: Discussionsupporting
confidence: 76%
“…The primary focus of this work was on the effects of TMAO upon the BBB, but this is not necessarily the only CNS target for the methylamine. Our data add to the evidence suggesting that astrocytes [ 66 , 67 ] and microglia [ 68 , 69 ] may respond to TMAO treatment, although it is notable that previous studies have shown pro-activating effects of TMAO at supra-physiological concentrations (> 50 μM). An intriguing finding of the current study is the brain region selectivity in the effects of long-term LPS and/or TMAO treatment upon parenchymal glia, with astrocytes and microglia of the entorhinal cortex showing clear LPS-induced, TMAO-sensitive activation, whereas the same cell types in the neighbouring hippocampus appeared resistant to either stimulus.…”
Section: Discussionsupporting
confidence: 76%
“…The primary focus of this work was on the effects of TMAO upon the BBB, but this is not necessarily the only CNS target for the methylamine. Our data add to the evidence suggesting that astrocytes [66,67] and microglia [68,69] may respond to TMAO treatment, although it is notable that previous studies have shown pro-activating effects of TMAO at supraphysiological concentrations (>50 µM). An intriguing finding of the current study is the brain region selectivity in the effects of long-term LPS and/or TMAO treatment upon parenchymal glia, with astrocytes and microglia of the entorhinal cortex showing clear LPS-induced, TMAO-sensitive activation, whereas the same cell types in the neighbouring hippocampus appeared resistant to either stimulus.…”
Section: Discussionsupporting
confidence: 77%
“…TMAO, SCFAs and Trp are three bacterial metabolites that have been shown to be associated with stroke [48][49][50]. TMAO is the product of some dietary nutrients, such as L-carnitine, phosphatidylcholine and choline, processed by intestinal microorganisms and transformed by heparin monooxygenase [51].…”
Section: Discussionmentioning
confidence: 99%